Antibiofilm and cytotoxic metabolites from the entomopathogenic fungus Samsoniella aurantia - Toshe, Rita; Khalid, Syeda J.; Kemkuignou, Blondelle Matio; Charria-Girón, Esteban; Eckhardt, Paul; Sandargo, Birthe; Nuchthien, Kunlapat; Luangsa-ard, J. Jennifer; Opatz, Till; Schrey, Hedda; Ebada, Sherif S.; Stadler, Marc (Beilstein Journal of Organic Chemistry, 2025)
During the course of our studies on the secondary metabolism of rare, hitherto untapped Thai insect-associated fungi, the ethyl acetate (EtOAc) extract derived from solid-state cultivation of Samsoniella aurantia on rice afforded one previously undescribed tetramic acid derivative, farinosone D (1), along with the known 2-pyridones, farinosones A (2) and B (3), and the known cyclodepsipeptides beauvericins A–C (4–6). All isolated compounds were assessed for their antimicrobial and cytotoxic activities while farinosones D (1) and A (2) were selected for biofilm inhibitory activity assay. Farinosone B (3) and beauvericins A–C (4–6) showed significant cytotoxic activities with IC50 values in the low micromolar to nanomolar range against several mammalian cell lines. On the other hand, farinosone A (2), which lacked potent cytotoxic effects, revealed potent antibiofilm activity, inhibiting approximately 70% of Staphylococcus aureus biofilms at concentrations as low as 3.9 µg/mL.
Keywords: antibiofilm; antiproliferative; beauvericin; insect pathogen; Samsoniella